2009
DOI: 10.1530/rep-08-0257
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ovulation by a lipoxygenase inhibitor involves reduced cyclooxygenase-2 expression and prostaglandin E2 production in gonadotropin-primed immature rats

Abstract: Potential roles of cyclooxygenase (COX) pathway of arachidonic acid (AA) metabolism are established in a murine model of induced ovulation. Pharmacological inhibition of an alternative lipoxygenase (LOX) pathway has been shown to cause defective ovulation, but the mechanism is still undefined. This study investigated the effects of two LOX inhibitors and their time dependency on ovulation and COX activity in gonadotropins (eCG and human chorionic gonadotropin (hCG))-primed immature rats. Intra-ovarian bursal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 40 publications
(55 reference statements)
1
22
0
Order By: Relevance
“…Other LOX enzymes including 5-and 12-LOX have also been reported in term uteroplacental tissues (Corriveau et al 2010). LOX enzymes are also detected in the theca and granulosa layers of rat pre-ovulatory ovarian follicles (Kurusu et al 2009). Direct evidence for altered resolution mediator signalling in pregnancy is provided by a recent report that LXA 4 levels are significantly elevated in serum from pregnant compared with non-pregnant women (Maldonado-Pérez et al 2010).…”
Section: Eicosanoid and U-3 Pufa Derived Resolution Mediatorsmentioning
confidence: 96%
See 1 more Smart Citation
“…Other LOX enzymes including 5-and 12-LOX have also been reported in term uteroplacental tissues (Corriveau et al 2010). LOX enzymes are also detected in the theca and granulosa layers of rat pre-ovulatory ovarian follicles (Kurusu et al 2009). Direct evidence for altered resolution mediator signalling in pregnancy is provided by a recent report that LXA 4 levels are significantly elevated in serum from pregnant compared with non-pregnant women (Maldonado-Pérez et al 2010).…”
Section: Eicosanoid and U-3 Pufa Derived Resolution Mediatorsmentioning
confidence: 96%
“…Pathways activated display extensive overlap with those regulated by resolution mediators including vascular changes, cytokine production, immune cell migration, apoptosis and ECM breakdown and repair. Both cyclooxygenase and LOX inhibition have been shown to suppress ovulation in the rat via inhibition of the LXA 4 inducer PGE 2 , and LOX expression in rat ovaries is enhanced by hCG induction of ovulation (Gaytan et al 2006, Kurusu et al 2009). More direct evidence for ovulation-associated resolution mediator production is provided by a peak in ovarian levels of the lipoxin precursor 15-HETE (Tanaka et al 1989).…”
Section: Resolution Pathways In the Ovarymentioning
confidence: 99%
“…17 Selective inhibition of the LOX pathway in rats significantly reduced the ovulation rate. 18 Recently, Kurusu et al 19 showed that both ALOX5 and ALOX12 expressed in thecal and granulosa layers of preovulatory follicles in rat and specific inhibition of LOX at an early stage of human chorionic gonadotropinYsignaling led to defective ovulation. Moreover, LOX has been reported to be associated with postmenopausal and many hormone-related diseases, such as osteoporosis, 20 Alzheimer disease, 21 cardiovascular disease, 22 and various reproductive tumors.…”
mentioning
confidence: 99%
“…It is known that the ovulation of sturgeon oocytes is induced by a gonadotropic pituitary hormone and progesterone. There are sufficient grounds to suggest that prostag landins participate in the induction of their ovulation, as is shown for tailless anuran amphibians (Schuetz, SKOBLINA, GONCHAROV 1986;Chang et al, 1995;Sena and Liu, 2008), bony fish (Goetz et al, 1989;Goetz and Garczynski, 1997;Lister and Van Der Kraak, 2008), and mammals (Hedin et al, 1987;Bridges et al, 2006;Kurusu et al, 2009).…”
mentioning
confidence: 96%